Blockade of a Key Region in the Extracellular Domain Inhibits HER2 Dimerization and Signaling. (17th April 2015) - Menendez, Javier A.; Schroeder, Barbara; Peirce, Susan K.; Vellon, Luciano; Papadimitropoulou, Adriana; Espinoza, Ingrid; Lupu, Ruth
Abstract : Background: Several treatment strategies target the human epidermal growth factor receptor 2 (HER2) in breast carcinomas, including monoclonal antibodies directed against HER2's extracellular domain (ECD) and small molecule inhibitors of its tyrosine kinase activity. Yet, novel therapies are needed that prevent HER2 dimerization with other HER family members, because current treatments are only partially effective. Methods: To test the hypothesis that HER2 activation requires a protein sequence in the HER2-ECD that mediates HER2 homo- and heterodimerization, we introduced a series of deletion mutations in the third subdomain of HER2-ECD. These deletion mutants were retrovirally expressed in breast cancer (BC) cells that naturally overexpress HER2 and in noncancerous, HER2-negative breast epithelial cells. One-factor analysis of variance or Student's t test were used to analyze differences. All statistical tests were two-sided. Results: The smallest deletion in the ECD domain of HER2, which removed only 16 amino acids (HER2-ECDΔ451–466), completely disrupted the oncogenic potential of HER2. In contrast to wild-type HER2, the mutant-inhibited anchorage-independent growth (mean number of colonies: mutant, 70, 95% confidence interval [CI] = 55 to 85; wild-type, 400, 95% CI = 320 to 480, P < .001) increased sensitivity to paclitaxel treatment in both transformed and nontransformed cells. Overexpression of HER2Δ451–466 efficiently inhibited activation of HER1, HER2, and HER3 in all cell lines tested. Conclusions: These findings reveal that an essential "activating" sequence exists in the extracellular domain of HER2. Disruption of this sequence disables the HER2 dimerization loop, blocks subsequent activation of HER2-driven oncogenic signaling, and generates a dominant-negative form of HER2. Reagents specifically against this molecular activation switch may represent a novel targeted approach for the management of HER2-overexpressing carcinomas.